STUDY ON GRADUATES OF THE FACULTY OF PHYSICAL EDUCATION AND SPORT OF GALATI WHO ENTERED THE LABOUR MARKET - Iconomescu Teodora Mihaela; Talaghir Laurentiu Gabriel; Badau Dana (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
During the 90's, graduates benefited of a high social status and living standards, currently the quality and value of a university degree is uncertain. Since the labour market has diversified significantly, an imbalance occurred between the labour market supply and demand. Therefore universities and faculties should establish a dialogue with the main beneficiaries on the labour market. Over the last years, this field of Physical Education and Sport has diversified considerably, at the same time the labour market demand has needed various other sport-related jobs whereas the Physical Education teacher job is no longer sought-after on the labour market. Consequently the degree programmes offered by faculties should be based on the demand from the labour market.